2021
DOI: 10.18240/ijo.2021.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin on diabetic retinopathy and its association with NLRP3 inflammasome and autophagy

Abstract: AIM: To investigate the effects of quercetin on diabetic retinopathy (DR) and its association with nucleotide-binding oligomerization domain-like receptors 3 (NLRP3) inflammasome and autophagy using retinal endothelial cell as an experimental model. METHODS: Human retinal microvascular endothelial cells (HRMECs) were cultured in vitro and assigned into the control group, high-glucose (HG) group, and HG+different concentrations of quercetin groups. Cellular viability, migration, and tube formation in these grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…In subsequent studies, GHSR-1a siRNA was used to block the effect of ghrelin. The results showed that the viability of HRMECs in the high-glucose group was significantly reduced, consistent with our previous results [ 26 ]. The viability of cells treated with exogenous ghrelin was significantly greater than that of cells in the high-glucose group.…”
Section: Discussionsupporting
confidence: 92%
“…In subsequent studies, GHSR-1a siRNA was used to block the effect of ghrelin. The results showed that the viability of HRMECs in the high-glucose group was significantly reduced, consistent with our previous results [ 26 ]. The viability of cells treated with exogenous ghrelin was significantly greater than that of cells in the high-glucose group.…”
Section: Discussionsupporting
confidence: 92%
“…In ischemic or traumatic brain cells, binding of glibenclamide to SUR1-TRPM4 reduces depolarization, which reduces blood–brain barrier breakdown and vasogenic edema [ 42 ]. In addition, in the retina, glibenclamide anti-edematous effects could result from the inhibition of the NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome and related neuroinflammation [ 43 ], known to be involved in diabetic retinopathy mechanisms [ 44 , 45 , 46 ]. In clinical studies, whether glibenclamide or other sulfonylurea drugs could improve the management of patients with diabetic macular edema has not been demonstrated, but the present result could prompt further studies on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin promotes and protects the function of the intestinal tight junction barrier ( 25 ) and degrades some intestinal bacteria, decreasing their amount in a time-dependent manner ( 26 ). It also protects human retinal microvascular endothelial cells from the high-glucose-induced injury by inhibiting the expression of NLRP3, caspase-1, IL-1 β, and IL-18 ( 27 ) and inhibits the expression of NLRP3, caspase-1, iNOS, and inflammatory factors in the LPS-activated mononuclear macrophages, consequently improving their antioxidant and anti-inflammatory abilities ( 28 ). Therefore, quercetin protects the integrity of the tight junction barrier and exerts a regulatory effect on the NLRP3 inflammasome.…”
Section: Popular Scientific Summarymentioning
confidence: 99%